বাংলাদেশ বাঙালি মানস রাষ্ট্রগঠন ও আধুনিকতা - মামুন, মুনতাসীর 1951- (ঢাকা: সময় প্রকাশন, 2007)
Articles on cultural history of Bangladesh and erstwhile Bengal, India.
Includes bibliographical references (p. 69-85).
In Bengali.
Keywords: Bangladesh -- Civilization; Bengal (India) -- Civilization